Perceptions of the quality of life among low and medium-cost housing community in Penang Island, Malaysia - Badarulzaman, Nurwati; Fawzi Bahaudin, Mohamed Amiruddin; Othman, Abdul Ghapar (2008)
This paper examines perceptions of the Quality of Life (QoL) among households residing in low and medium-cost housing areas in Penang Island, Malaysia. The term QoL is vague and subjective with little consensus on what factors to be included for analysis. Nonetheless, the QoL concept needs to be defined by its components and attributes, which include the subjective dimensions and the objective realities. Literature on the quality of life in cities and neighborhoods have identified several indicators that are believed to represent quality and contributing towards residential satisfaction. City residents have generally voiced concerns about problems caused by unabated growth. The introduction of certain measures of quality of life in urban neighbourhoods may help monitor and gauge the neighbourhood profile and livability. A broader definition of QoL could capture such changes towards improving the quality of life in urban neighbourhoods. This study investigates perceptions of the quality of life among residents living in fifteen urban neighbourhoods in Georgetown and Bayan Lepas, Penang. The study focuses on four aspects of quality of life, namely housing, housing environment, public transport and public safety. Results from a questionnaire survey of 337 respondents revealed that both Georgetown and Bayan Lepas residents were not satisfied with their housing and housing environment. They were unhappy with public transport, and were worried about the level of public safety in their housing areas. Efforts should be undertaken to address these issues to improve the quality of life in these neighbourhoods.